Culture and Role of Women's Leadership in the Cameroon Region - Taoyang, Obu Douma (oneamd.com, 2025)
The topic of gender studies, especially regarding women's roles in politics, is becoming more prominent in academic discussions in Cameroon, particularly in the northern region. Although women make up over half of the population in the north, they mainly engage in politics as voters and supporters in political activities, especially concerning political leadership in this area. They handle most of the tasks related to mobilizing for campaigns. However, women in the north face numerous obstacles that hinder their full participation in political leadership. These challenges include restrictive cultural norms, unfair traditional laws, and a deeply divided household workload. This paper looks into the different social and cultural challenges that hold women back from fully engaging in political leadership and decision-making. Since democracy began in Cameroon, cultural obstacles, social restrictions, and religious limitations have made it difficult for women to enter political leadership roles